Optimasi Tata Ruang Dalam Meningkatkan Kenyamanan Budaya Baca Pemustaka di Perpustakaan Jusuf Kalla Universitas Islam Internasional Indonesia - Audrey Marchanda Putri; Raziq Hasan (PT. Hasba Edukasi Mandiri, 2025)
Library spatial planning plays a crucial role in creating comfort and supporting the reading culture of users. This study examines the optimization of the spatial arrangement of the Jusuf Kalla Library at UIII to enhance efficiency, accessibility, and the appeal of reading spaces. Using a qualitative descriptive approach, this research evaluates zoning, lighting, circulation, and ease of access to collections and supporting facilities. The results indicate that natural lighting, clear zoning, and digital technology integration can enhance user comfort. Flexible zoning allows users to choose spaces according to their needs, whether for individual study or group discussions. However, limitations in accessibility, space efficiency, and operational hours remain challenges. As a solution, this study recommends optimizing spatial planning through a more dynamic design, improved accessibility, and the utilization of smart technology to enrich user experiences. This optimization is expected to serve as a model for modern libraries that are more functional and attractive.